Characteristics of Internal Solitary Waves near Its Generation Site in the Lombok Strait, Indonesia - Purwandana, Adi; Edikusmanto, Edikusmanto; Utari, Putri Adia; Lestiana, Hilda; Saputra, Okta Fajar; Sari, Qurnia Wulan (POSITRON, 2023)
Evidence of internal solitary waves (ISWs) formation through the Lee wave mechanism in the Lombok Strait was revealed from the echosounder measurements conducted in November 2017. This study is aimed to characterize the property of ISW packet formed around ~30 km away from the generation site, in the southern part of the strait above the Nusa Penida Sill (NPS), by employing Korteweg-de Vries (KdV) solution. The packet can be categorized as the early stage of ISW formation, consisting of two waves of depression, with typical amplitude of 30 m and 10 m, for the first and second wave, respectively. The waves propagated northward with a typical phase speed of ~1.2 m∙s -1. The waves drive a maximum horizontal velocity anomaly of ~0.8 m∙s - 1 and a vertical velocity anomaly of ~10 cm∙s -1. The amplitude of the ISW packet will be potentially amplified during their propagation away from the strait. This study provides an observational based understanding on the early stage of internal tides evolution in the Lombok Strait, particularly highlights the energy transfer of internal tides through the propagation of internal solitary waves.